Genetic diagnosis of inborn errors of immunity using clinical exome sequencing - Kwon, Soon Sung; Cho, Youn Keong; Hahn, Seungmin; Oh, Jiyoung; Won, Dongju; Shin, Saeam; Kang, Ji-Man; Ahn, Jong Gyun; Lee, Seung-Tae; Choi, Jong Rak (Frontiers in Immunology, 2023)
Inborn errors of immunity (IEI) include variety of heterogeneous genetic disorders in which defects in immune system lead to an increased susceptibility to infections and other complications. Accurate, prompt diagnosis of IEI is crucial for treatment plan and prognostication. In this study, clinical utility of clinical exome sequencing (CES) for diagnosis of IEI was evaluated. For 37 Korean patients with suspected symptoms, signs or laboratory abnormalities associated with IEI, CES which cover 4,894 genes including genes related with IEI were performed. Their clinical diagnosis, clinical characteristics, history of infection and family, laboratory results as well as detected variants were reviewed. With CES, genetic diagnosis of IEI was made in 15 patients among 37 patients (40.5%). 17 pathogenic variants were detected from IEI-related genes, BTK, UNC13D, STAT3, IL2RG, IL10RA, NRAS, SH2D1A, GATA2, TET2, PRF1 and UBA1, of which four variants were previously unreported. Among them, somatic causative variants were identified from GATA2, TET2 and UBA1. In addition, we identified two patients incidentally diagnosed IEI by CES performed to diagnose other diseases of patients with unrecognized IEI. Taken together, these results demonstrate the utility of CES for the diagnosis of IEI, which contributes to accurate diagnosis and proper treatments.